1986
DOI: 10.1111/j.1476-5381.1986.tb10250.x
|View full text |Cite
|
Sign up to set email alerts
|

False labelling of dopaminergic terminals in the rabbit caudate nucleus: uptake and release of [3H]‐5‐hydroxytryptamine

Abstract: nomifensine (1, 10 gAM) reduced the tritium accumulation to 65% whereas 6-nitroquipazine (1 JM) was ineffective. The combination of both drugs (1 JAM each) led to a further decrease to about 15%.3 The uptake of [3H]-dopamine into hippocampal slices was blocked by both nomifensine (I JM) and 6-nitroquipazine (I ILM) whereas in caudate nucleus slices only nomifensine (1, 1OtM) reduced the accumulation of [3H]-dopamine. The combination of both drugs was not more effective than nomifensine alone. The different eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 16 publications
(23 reference statements)
2
29
0
Order By: Relevance
“…The selectivity of citalopram is the greatest among SSRIs; the K i values for 5-HT, NE, and DA are 14 nM, 32 M, and 41 M, respectively (Hyttel, 1977); therefore, at the concentration (1 M) used in our experiments, only the SERT was effectively inhibited. The hippocampus is densely innervated by noradrenergic and serotonergic varicosities but contains only sparse dopaminergic innervation; the ratio is 30:25:1 for 5-HT/NE/DA (Feuerstein et al, 1986). The average densities of serotonergic (Oleskevich and Descarries, 1990) and noradrenergic (Oleskevich et al, 1989) varicosities are 2.7 and 2.1 million/mm 3 , respectively.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The selectivity of citalopram is the greatest among SSRIs; the K i values for 5-HT, NE, and DA are 14 nM, 32 M, and 41 M, respectively (Hyttel, 1977); therefore, at the concentration (1 M) used in our experiments, only the SERT was effectively inhibited. The hippocampus is densely innervated by noradrenergic and serotonergic varicosities but contains only sparse dopaminergic innervation; the ratio is 30:25:1 for 5-HT/NE/DA (Feuerstein et al, 1986). The average densities of serotonergic (Oleskevich and Descarries, 1990) and noradrenergic (Oleskevich et al, 1989) varicosities are 2.7 and 2.1 million/mm 3 , respectively.…”
Section: Discussionmentioning
confidence: 89%
“…The connection between dopaminergic and serotonergic uptake has also been described. It has been shown that dopaminergic terminals take up and release [ 3 H]5-HT in the striatum and serotonergic varicosities take up and release [ 3 H]DA in the hippocampus of rabbit (Feuerstein et al, 1986). A paper reported that cocaine place preference persists in DAT or SERT KO mice, but disappears in combined DAT/ SERT KO animals, suggesting that both systems contribute to the rewarding effects of cocaine (Sora et al, 2001).…”
Section: Presynaptic Modulation Of Norepinephrine Releasementioning
confidence: 99%
“…These results strongly suggest that the effect of serotonin on basal 3H overflow is not mediated by serotonin receptors, but appears to involve the DA re-uptake carrier. Serotonin can be transported by the DA reuptake carrier (27,28) and could thus enhance…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 5-HT 3 receptor is a good candidate for modulation of dopamine. However, interaction of 5-HT with carrier-mediated mechanisms via the DA transporter have also been well documented (Feuerstein et al 1986;Schmidt and Black 1989;Yeghiayan et al 1997;Yi et al 1991).…”
Section: Discussionmentioning
confidence: 99%